The Effect of Nitrogen and Sulfur Addition on Bioethanol Solid Waste Fermented by the Consortium of Trichoderma viride and Saccharomyces cerevisiae towards Dry Materials, Organic Materials, Crude Protein and Non Nitrogen Protein - Suryani, Yani; Hernaman, Iman; Rochana, Ana; Setiawati , Ayu; Paramarta, Gilang Dayinta; Andayaningsih , Poniah (Asian Journal of Agriculture and Rural Development, 2013)
The aim of this study is to determine the effect of supplementation of nitrogen and sulfur in Bioethanol solid waste fermentation by a consortium of Trichoderma viride and Saccharomyces cerevisiae to dry matter, organic matter, crude protein and non-protein nitrogen. Experimental design used was a complete-random design factorial 3x3 patterns. The treatment consists of; first factor (N1 = 0%, N2 = 1.5%, N3 = 3%) and the second factor (S1 = 0%, S2 = 0.02%, S3 = 0.04%) in which each treatment was repeated three times. The results showed that there was an interaction in the Bioethanol solid waste which was fermented by a mixture of Trichoderma viride and Saccharomyces cerevisiae on dry matter and organic matter. The addition of nitrogen at a dose of 3% produced dry matter and organic matter within the average value of 65.56% and 63.81%. The addition of sulfur at a dose of 0.04% produced dry matter and organic matter within the average value of 59.67 and 57.58%. The addition of 1.50% nitrogen without giving sulfur can increase the crude protein content of the substrate (P <0.05) significantly, whereas the non-protein nitrogen content of each treatment have different effects and not real. The results showed 1.5% urea to provide optimal results.